The Environmental Perspectives of Apple Fruit Supply Chain Management in Chitral, Northern Pakistan - Khan, Muhammad; Bae, Jung Han (International Journal of Supply Chain Management, 2017)
Abstract- With increasing population the demand for fresh fruits is on the rise in Pakistan. Because of perishing nature and short shelf life, fruits require proper and effective supply chain management (SCM) for securing them to be wasted. Fruits of Chitral, Northern Area of Pakistan face supply chain (SC) issues and challenges. The main purpose is to conduct a detailed insight of the present apple fruit SCM system in Chitral for identifying the related environmental perspective of apple. That small subsistence farming should be view as a business. As compare to the producers’ income with others intermediaries, (27% to 73%) it is significantly lower. Focus should be given that the distribution of the marketing margin across the players can be measured fairly. The anticipated research work is exploratory in nature using secondary data, undertakes a meticulous review of basic and up to date literature available and tried to explain the factors affect the supply chain of Apple Fruit sector in Chitral, Northern Area of Pakistan.